The Role of the Government in the Development of Indonesian Sharia Banking (Journal of Private and Commercial Law, 2021)
The growth of the Sharia financial industry in Indonesia is quite slow, this is due to the lack of the government's role in helping develop the Islamic finance industry, even though the potential of the Islamic banking market in Indonesia is actually very large. Therefore, the purpose of this study is to discuss the issue of whether the economic values of Sharia are in accordance with Indonesian philosophy and values, so that the Sharia Industry is able to develop fundamentally in Indonesian society, as well as how the role of the government is to provide a strong basis in developing the Islamic Banking Industry in Indonesia. Indonesia. Because the progress of Islamic banking as a financial industry determines its development in the economy in Indonesia. This study uses a normative research method, where research is focused on legal norms or norms. In the development of Islamic banking by the government, it involves several institutions as the means. The scope of cooperation coordination is broad in order to make Indonesia the center of Islamic economics and finance Some of these institutions include: Bank Indonesia, the Financial Services Authority and the Sharia Supervisory Board. Each institution carries out its role in order to achieve the objectives of developing Islamic banking which have been arranged in a development management.